Benefit-cost trade-offs-based empathic choices. (January 2023) - Ge, Yabo; Li, Xinyu; Li, Fengying; Chen, Fangyan; Sun, Binghai; Li, Weijian
Abstract: Empathy often confers benefits and entails costs. However, how individuals choose empathy, which involves both benefits and costs, remains unclear. This study proposes a possible mechanism underlying empathic choices 1 : benefit-cost trade-offs. Studies 1 and 2 adopted empathy selection tasks and manipulated empathic benefits and costs to examine its effects on reaction times of empathic choices. In Study 3, an empathy experience writing task was developed and the impact of the difference between benefits and costs on the difficulty of empathic choices was examined. Results showed that participants' reaction times of empathic choices for strangers were significantly slower than for friends (Study 1); however, this effect disappeared when the benefits toward strangers increased (Study 2). Furthermore, the difficulty of empathic choices was significantly and negatively predicted by the difference between benefits and costs (Study 3). The implications of this study and its future directions are discussed. Highlights: Empathy is often a choice which involves both benefits and costs. Empathic choices are made after a consideration of benefit-cost trade-offs. People choose empathy because it is worth doing.